Il cannocchiale di Tristano: Il “vedere” e il “guardare” nel Tristano muore di Antonio Tabucchi - Lukácsi, Margit (Verbum – Analecta Neolatina, 2016)
The paper analyses Antonio Tabucchi’s last novel, Tristani muore. It argues that in this novel too, Tabucchi leads the reader on the border of reality and imaginaton. We can observe all through the novel the references to visuality, various works of art, photographies. The paper highlights the essence of Tabucci’s writing through the meanings of the verbs vedere ‘see’ and guardare ‘look’.